Uwzględnianie rozsądnych życzeń małoletniego jako wyraz zasady dobra dziecka w sprawach opiekuńczych dotyczących kontaktów z dzieckiem - Sikora, Paulina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
This article is devoted to analysis of the position of a juvenile, with particular emphasis on its actual impact on the court’s decision in the matters of contact with a child. At the beginning, an attempt to indicate the problems associated with the use of current regulations was made. Then, legal concepts and institutions that play an important role in assessing the importance of the child in the given context were discussed. The aim of the article is to answer the question whether the current legal standing allows for the realization of the constitutional goodness of the child principle, especially in the aspect of taking into account the reasonable wishes of the juvenile.
Keywords: children; legal proceedings; family law; reasonable wishes; hearing a juvenile